Regulatory Rigor Or Rights Denied? - A Critical Examination Of Adoption Protocols For Abandoned Children In India (International Journal of Environmental Sciences, 2025)
India's adoption landscape is marked by a complex interplay between regulatory frameworks and child welfare imperatives. Despite a substantial population of abandoned and orphaned children, the number of successful adoptions remains disproportionately low. This research critically examines whether the rigorous adoption protocols established under Indian law, primarily governed by the Juvenile Justice (Care and Protection of Children) Act, 2015 and overseen by the Central Adoption Resource Authority (CARA), safeguard the rights of abandoned children or inadvertently hinder their access to a nurturing family environment. The research explores the procedural requirements for declaring a child legally free for adoption, the bureaucratic challenges faced by Child Welfare Committees (CWCs), and systemic inefficiencies in institutional mechanisms such as the CARINGS portal. Drawing on instances and views, this research argues that while regulatory oversight is essential to prevent trafficking and ensure ethical adoption practices, the current system often results in prolonged institutionalization, violating a child’s right to family and development. The research further situates India’s adoption protocols within an international human rights framework, including obligations under the United Nations Convention on the Rights of the Child (UNCRC). It proposes a set of reforms aimed at balancing protection with expediency, streamlining processes, standardizing protocols across states, and ensuring timely judicial and administrative action. This research delineates that true child welfare lies not in procedural perfection but in responsive, rights-based governance that places the best interest of the child at the heart of adoption policy.